In vitro isolation of a gamma ray induced mutant in chrysanthemum (Dendranthema grandiflora) - ANAND, PRATIVA; VANLALRUATI, VANLALRUATI; KUMAR, GUNJEET; KUMAR, SURENDRA (The Indian Journal of Agricultural Sciences, 2020)
In the present investigation, an effort was made to develop an efficient ray floret regeneration protocol in order to isolate, purify and establish a novel gamma ray induced mutant in the form of brick red flowers in chrysanthemum (Dendranthema grandiflora Tzvelev.) cv. Tata Century (pink). Maximum survival (60.00%) and callus formation (56.60%) in minimum duration (10.20 days) were recorded when the ray florets were pre-treated with carbendazim (0.2%) + ridomil (0.2%) + 8-HQC (200 mg/l) for 2 h followed by surface sterilization with HgCl2 (0.1%) for a duration of 4 min and cultured on MS medium supplemented with BAP (4.0 mg/l) and NAA (1.0 mg/l). The maximum regeneration of microshoots (66.00%) from the ray floret induced callus was recorded on MS medium fortified with BAP (4.0 mg/l) + NAA (1 mg/l). MS medium supplemented with BAP (4.0 mg/l) + NAA (0.05 mg/l) + GA3 (0.1 mg/l) was found to be best for highest micro-shoot proliferation (80.00%). Highest rooting (87.60%) was induced after inoculating the microshoots individually on half-strength MS medium fortified with 0.5 mg/l NAA and 60 g/l sucrose. Successful acclimatization of in vitro raised plantlets was done in glass jar with polypropylene cap each filled with a mixture of sterilized cocopeat, soilrite and perlite (1:1:1 v/v) supplemented with half-strength MS inorganic salts. After 3-4 weeks of acclimatization the plantlets were successfully transferred to field conditions.